Measurements of global and local spin polarization of Λ and Λ in Au+Au collisions from the RHIC Beam Energy Scan - Hu Qiang (EPJ Web of Conferences)
We report the measurements of Λ hyperons’ global and local spin polarization from second phase of the RHIC Beam Energy Scan (BES-II) in Au+Au collisions at Λ and Λ¯ = 7.7−27 GeV. Global polarization measurements of Λ and Λ show no significant differences, offering insights into the late-stage evolution of the magnetic field. The new measurements of the local polarization of Λ perpendicular to the reaction plane (<P2,y>) shows a monotonic increase with decreasing collision energy, while the component along the beam direction (<P2,y>) for both Λ and Λ is small in magnitude with no strong energy dependence. The net local polarization observable, Λ and Λ¯ and 〈P2,ynet> = 〈P2,y(Λ)〉 - 〈P2,y(Λ¯)〉 and 〈P2,znet〉 = 〈P2,z(Λ)〉 - 〈P2,z(Λ¯)〉 designed to probe baryonic spin Hall effect, is consistent with zero with large uncertainty.